Development of functionalized peptides for efficient inhibition of myostatin by selective photooxygenation. Issue 1 (11th November 2020) - Okamoto, Hideyuki; Taniguchi, Atsuhiko; Usami, Shoya; Katsuyama, Masahiro; Konno, Sho; Taguchi, Akihiro; Takayama, Kentaro; Hayashi, Yoshio
Abstract : Functionalized peptides which consist of myostatin-binding peptide and on/off-switchable catalyst efficiently inhibit myostatin by selective photooxygenation, leading to a therapeutic strategy for muscular atrophic disorders. Abstract : For the inhibition of myostatin, which is an attractive strategy for the treatment of muscle atrophic disorders including muscular dystrophy, myostatin-binding peptides were synthesized with an on/off-switchable photooxygenation catalyst at different positions on the peptide chain. These functionalized peptides oxygenated and inactivated myostatin upon irradiation with near-infrared light. Among the peptides tested, a peptide (5 ) with the catalyst moiety at the 16 position induced myostatin-selective photooxygenation, and efficiently inhibited myostatin. These peptides exhibited low phototoxicity. Such functionalized peptides would provide a precedented strategy for myostatin-targeting therapy, in which myostatin is irreversibly and catalytically inactivated by photooxygenation.